Visual outcomes after implantation of a novel refractive toric multifocal intraocular lens - Shimoda,Talita (2014)
Purpose: To assess the postoperative outcomes of a novel toric multifocal in traocular lens (IOL) in patients with cataract and corneal astigmatism. Methods: This prospective nonrandomized study included patients with cataract, corneal astigmatism, and a motivation for spectacle independence. In all patients, a Rayner M-flex® T toric IOL was implanted in the capsular bag. Three months after surgery, the distance, intermediate, and near visual acuities; spherical equivalent; residual refractive astigmatism; defocus curve; and contrast sensitivity were evaluated. A patient satisfaction and visual phenomena questionnaire was administered to all patients. Results: Thirty-four eyes of 18 patients were included in this study. Three months after surgery, the mean corrected distance visual acuity (logMAR) was 0.00 ± 0.08 at 6 m, 0.20 ± 0.09 at 70 cm, and 0.08 ± 0.11 at 40 cm. Uncorrected distance vision acuity was 20/40 or better in 100% eyes. The preoperative mean refractive cylinder (RC) was -2.19 (SD: ± 0.53). After a 3-month follow-up, the average RC was -0.44 D (SD: ± 0.27; p<0.001). Contrast sensitivity levels were high. At the last follow-up, 87.5% patients were spectacle-independent for near, intermediate, and distance vision, and approximately 44% patients reported halos and glare. Conclusion: Toric multifocal IOL implantation in patients with cataract and corneal astigmatism using the Rayner M-flex® T toric IOL was a simple, safe, and accurate option. This technology provides surgeons with a feasible option for meeting patient expectations of an enhanced lifestyle resulting from decreased spectacle dependence.